PENGELOLAAN KEUANGAN DANA DESA DI DESA KOTO TANDUN KECAMATAN TANDUN KABUPATEN ROKAN HULU TAHUN 2019-2020 - Anisa Armayanti; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study intends to examine how effective the management of the Village Fund is in improving the physical development of the village in the Koto Tandun Village area which is one of the villages in the Tandun District, Rokan Hulu Regency. Koto Tandun Village requires a lot of funds for development in order to prosper its people, thus Koto Tandun Village must be more creative and innovative in utilizing village funds for the benefit of government administration, village development and village community services so that they are right on target. This research is important to do to provide an overview of the effectiveness of the financial management of Village funds in development, both in the form of physical development in this case facilities and infrastructure as well as community empowerment in the village, especially in Koto Tandun Village, Tandun District, Rokan Hulu Regency. The type of research chosen is a descriptive research type with a qualitative approach. Data collection techniques used are literature study and field study (observation and interviews). The research informants were the Village Head, Head of Financial Affairs, Head of BPD, Head of Government Section and residents of Koto Tandun Village. The results of the study prove that the effectiveness of Village Fund Management in Koto Tandun Village so far, the management can be said to be effective, although it still needs to be improved and there are still obstacles that must be fixed for the progress of village development. Keywords: Effectiveness, Village Fund Financial Management